Recent advances in nuclear medicine and their role in inflammatory arthritis: focus on the emerging role of FAPI PET/CT - Schmidkonz, Christian; Kuwert, Torsten; Götz, Theresa Ida; Ramming, Andreas; Atzinger, Armin (Skeletal Radiology, 2024)
Imaging molecular processes associated with inflammatory disease has been revolutionized by hybrid imaging using positron emission tomography/computed tomography (PET/CT). PET/CT visualizes metabolic activity as well as protein expression and provides a comprehensive whole-body evaluation. It has the potential to reveal inflammation prior to detection of structural changes in inflammatory joint diseases. FAP is a type II transmembrane glycoprotein overexpressed not only in the stroma of tumors but also in the fibrotic processes of certain immune-mediated disorders. The recent introduction of fibroblast activation protein inhibitors (FAPI) labeled by positron emitters and thus suitable for PET/CT allows to investigate FAP expression in vivo. This review will focus on the use of FAPI-PET/CT for the diagnosis and evaluation of treatment response in inflammatory joint diseases.
CRIS-Team Scopus Importer:2025-02-04
Keywords: FAPI; Joint diseases; Molecular imaging; PET/CT